ANALISIS POLYMETRIC PADA MUSIK IRINGAN TARI NGERUAI KENEMIAK SUKU DAYAK KANTU’ KAPUAS HULU - Firman, Ridho; Ismunandar, Ismunandar; Silaban, Christianly Yery (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbsractThis research is based on the willingness of the researcher to find out the polymetric in music?s acompaniment of Ngeruai Kenemiak dance of Dayak Kantu? tribe, Kapuas Hulu. Polymetric is the use of two different time signature signs of each instrument that played simultaneously in one composition. The purposes of this research are: 1) The descriptioning of the structure of music?s acompaniment of Ngeruai Kenemiak dance of Dayak Kantu? tribe, Kapuas Hulu, 2) The analysis of the polymetric in music?s acompaniment of Ngeruai Kenemiak dance of Dayak Kantu? tribe, Kapuas Hulu. A method used in this research is analysis descriptive method with musicological approachment. The data is analyzed qualitatively. According to the data analysis, music?s accompaniment of Ngeruai Kenemiak has four parts: tebah bujang berani in the opening, tebah kumang gaga in the middle?, and tebah ansing-ansing in the ending. The polymetric used in the composisition composed by the use of time signature signs in gerumong  instrument 5/4 and 3/4 are different with what used in bebenai, tawak, and ketebong instruments (4/4). The difference of the time signature signs are played altogether in one composition with same tempo. Keywords: Dayak Kantu?, Music Accompaniment, Ngeruai Kenemiak, Dance, Polymetric.